Plymouth Policewomen's Department - Stevenson, Kim (Law, crime & history, 2023)
This witness seminar was organised by the University of Plymouth in association with the Institute for Contemporary British History, King’s College, London. This forms part of the #CHITCHAT? Witness seminar series and the transcription was subsequently organised by Culture and Heritage Exchange (CHEx). This seminar captured the fascinating memories and stories of seven former policewomen who served in Plymouth City Policewomen’s Department in the 1950s and 1960s. It covers themes relating to the uniforms issued, training received, relationships with the public, operational duties and work undertaken.